Overall response to anti-IL-5/anti-IL5-Rα treatment in severe asthma does not depend on initial bronchodilator responsiveness - Mümmler, Carlo; Suhling, Hendrik; Walter, Julia; Kneidinger, Nikolaus; Buhl, Roland; Kayser, Moritz Z.; Drick, Nora; Behr, Jürgen; Welte, Tobias; Korn, Stephanie; Milger, Katrin (The journal of allergy and clinical immunology. In practice, 2022)
Positive bronchodilator responsiveness (BDR) (change in forced expiratory volume in 1 second [ΔFEV1] ≥ +200 mL and ≥ +12%) after inhalation of a short-acting beta-2 agonist has been an inclusion criterion in licensing trials of anti-interleukin 5/anti-interleukin 5 receptor alpha (anti-IL-5/anti-IL-5Rα) biologics in severe asthma. However, in clinical practice, patients with severe uncontrolled asthma frequently show a negative BDR. To investigate whether the response to anti-IL5/anti-IL5Rα therapies differs between patients with positive and negative BDR at baseline.
Dateiversion vom 7. Dezember 2022
Gesehen am 07.02.2023